Analysis of the Effects of Severe Voltage Unbalance on the DC Bus of a Variable Frequency Drive and DC Bus Passive Filtering Harmonic Mitigation - (:unkn) unknown (My University, 2013)
The power quality of a distribution system can greatly effect the way devices connected to that power source operate. Sometimes one poor power quality characteristic can lead to another poor power quality characteristic. In the case presented in this paper, severe voltage unbalance at the input of a variable frequency drive leads to increased harmonic content in the power distribution system and the device under operation. This paper addresses, in particular, the effects of severe voltage unbalance on the DC bus of a 6-pulse variable frequency drive. The steady-state balanced voltage harmonic behavior of the DC bus is analyzed along with standard filtering techniques used to mitigate the characteristic harmonics on the DC bus. The steady-state severe unbalanced voltage harmonic behavior of the DC bus is then analyzed and additional filtering techniques are then introduced to mitigate the non-characteristic harmonics on the DC bus that were produced by the severe voltage unbalance. Simulations of the balanced and unbalanced conditions mentioned above are presented in MATLAB$^\circledR$. Bode plots of the 6-pulse converter are then analyzed to measure the frequency response of the system under these conditions and the Fast Fourier Transform of different signals in the system are generated to graphically represent the harmonics in the system. Finally, experimental results will show the successful application of the filtering techniques, presented in this paper, on a 6-pulse variable.